NIR‐II emissive biohybrid nanovesicles as mild‐temperature photothermal antibiofilm agents against acute bacterial skin and skin‐structure infections - Ji Wang; Zhihao Wu; Xiaoxi Ma; Zhihui Huang; Haorong Dong; Jinxin Zhang; Xiaoming Liu; Pengfei Zhang; Shuhuai Yao (Interdisciplinary Medicine)
Abstract The emergence of antibiotic‐resistant bacteria poses a significant challenge to the prompt and appropriate treatment of pathogenic bacteria infections, such as acute bacterial skin and skin‐structure infections (ABSSSI), especially in the presence of biofilms. Bacterial biofilms are naturally resistant to antibiotics and the human immune system, making biofilm‐based infections extremely difficult to treat. Therefore, developing new antibacterial therapies targeting biofilms is crucial. Aggregation‐induced emission luminogens with fluorescence in the second near‐infrared window (NIR‐II AIEgens), which can be activated by a near‐infrared laser to generate heat, offer an effective and precise photothermal therapy (PTT) approach for treating deep‐tissue bacterial infections. However, the presence of biofilms impedes the entry of photosensitizers into the infected area, requiring higher drug doses and increasing the risk of PTT. Herein, we developed a biocompatible AIEgen‐based biohybrid nano formulation that incorporates the BPBBT (NIR‐II AIEgen) and antibiofilm α‐amylase into a red blood cell (RBC) membrane‐derived nanovesicle carrier for a PTT/biofilm degradation combination therapy. The synergistic effect of this new formulation enhances both the photothermal capability of BPBBT and the biofilm degradation compared to traditional individual treatments. The new combination therapy demonstrated significant improvement in treating severe Staphylococcus aureus infections caused by biofilms in vitro and in vivo, presenting a promising alternative to traditional antibiotic therapy.